MAKROEKONOMI DAN TINGKAT KESEHATAN BANK TERHADAP PERTUMBUHAN KREDIT PERBANKAN - Nabilah Putri Hanzari (2022)
Credit is a banking business activity in carrying out its function as an intermediary institution. This study aims to determine the effect of Macroeconomics, Domestic Deposit Growth, and Bank Health Level on Credit Growth at Conventional Banks KBMI 1 in 2017-2021. Sampling used purposive sampling and panel data regression techniques as analysis techniques which were processed using E-views 12. The results in this study show the BI Rate, Economic Growth, Domestic Deposit Growth, Loan to Funding Ratio, Return on Assets, and Capital Adequacy Ratio has a significant effect on credit growth, while Non Performing Loan have no significant effect on credit growth. Keywords: Macroeconomics, Domestic Deposit Growth, Credit Growth, Bank Health Level, Banks KBMI 1.